Quality of peanut mechanical sowing in function of seeding density and size of the seeds - Cristiano Zerbato; Carlos E. A. Furlani; Rodrigo F Almeida; Murilo A. Voltarelli; Vicente F. A. Silva (Engenharia Agrícola, 2015)
ABSTRACT Peanut crop (Arachis hypogaea L.) mechanization has been improved over the years; however there are drawbacks that affect the quality of operations. Thus, this article’s objectives were to evaluate the operational performance of the mechanized sowing of peanut crop according to seeding densities (10, 14, and 18 seeds m-1) and seed sizes (21 and 23 mm). It was observed that the seeds of 23 mm had shorter average number of days to emergence and a higher percentage of emergences, occurring the opposite to the seeding density of 18 seeds m-1. The higher the seeding density, the largest was the plant stand, whereas the 23 mm seed obtained the best results and the same with the seeding density of 14 seeds m-1 that had a higher percentage of normal spacing. The densities of 14 and 18 seeds m-1 reflected in higher yields, being always superior to the 23 mm seeds.